Pedestrian- & transit-oriented design - Ewing, Reid H. (Urban Land Institute, 2013)
"Explaining how to design spaces for pedestrians while also accommodating transit needs, this book is an excellent reference for students, public sector planners and officials, and private sector designers and developers seeking to make places more pedestrian- and transit-friendly. Written by a noted expert on pedestrian design and planning, this handbook contains examples of zoning codes from different localities"--